Efeitos de diferentes doses de ranelato de estrôncio isolado e associado à vibração mecânica de baixa intensidade na cartilagem articular de ratas ooforectomizadas - Mierzwa, Aline Gomes Hidalgo [UNIFESP] (2016)
To investigate the effects of different doses of strontium ranelate (SrR) alone or combined with low-intensity and high-frequency mechanical vibration (MV) on articular cartilage of ovariectomized rats. Methods: Fifty 6-month-old female Wistar rats underwent ovariectomy and after three months were divided into five groups: Control group: treated with vehicle solution; SrR300 group: treated with 300 mg/kg/day SrR; SrR625 group: treated with 625 mg/kg/day SrR; MV group: submitted to mechanical vibration; SrR625+MV group: treated with 625 mg/kg/day SrR and submitted to MV. The vehicle solution (water) and SrR were administered by gavage 7 days/week and mechanical vibration was performed during 20 min/day, 5 days/week in a platform set to provide a vertical acceleration of 0.6g at a frequency of 60 Hz. Bone mineral density (BMD) and body composition were evaluated by bone densitometry (DEXA) at the beginning and end of treatment. After 90 days, the animals were euthanized and the distal femurs with their cartilages were fixed in 4% formaldehyde (derived from paraformaldehyde) in 0.1 M phosphate buffer (pH 7.2), decalcified in EDTA 10% in a sodium phosphate buffer (pH 7.2), dehydrated in increasing ethanol concentrations, diaphanized in xylene, impregnated and embedded in paraffin. The serial sections were performed with 5 ?m thick, adhered to slides and subjected to Hematoxylin and Eosin staining for histomorphometric analyses, in order to check the number of chondrocytes and clusters. Some sections were submitted to immunohistochemistry to evaluate cell death (Caspase-3), tumor necrosis factor-? (TNF-?), matrix metalloproteinase 9 (MMP-9) and type II collagen. Others sections were graded according to osteoarthritis degree as proposed by OARSI (Osteoarthritis Research Society International) using Safranin O and Fast Green staining. For biochemistry analyses, the articular cartilage was removed from the distal femur and subjected to quantification of sulfated glycosaminoglycans by agarose gel electrophoresis and hyaluronic acid by ELISA. Results: Total mass and fat percentage increased in Control group, while SrR625 exhibited reduced fat percentage, increased lean mass and the highest BMD at the end of treatment. Strontium ranelate treated groups exhibited the lowest degree of osteoarthritis according to OARSI, smaller number of chondrocytes clusters, increased levels of chondroitin sulfate and decreased expression of caspase-3. The highest level of hyaluronic acid was observed in SrR300 group compared to all others groups. Mechanical vibration applied alone and/or combined accelerated the cartilage degradation as demonstrated by increased OARSI grade, reduced number of chondrocytes, increased number of clusters, elevated expression of type II collagen and cell death, accompanied by decreased amounts of chondroitin sulfate and hyaluronic acid. However, mechanical vibration alone was able to reduce TNF-? and MMP-9 expression. Conclusion: Taking together our results show that strontium ranelate and mechanical vibration modulate distinct responses in articular cartilage of ovariectomized rats. The degeneration process seems to be accelerated when the treatments are associated. On the other hand, SrR treatment at 300 mg/kg/day dose attenuates osteoarthritis progression, improving the cartilage matrix quality and preserving chondrocytes viability.